Analisis Persepsi Mahasiswa Terhadap Ketidakjujuran Akademik : Studi Kasus di Fakultas Teknik UNS - Andrye Sukma Wicaksono; Indah Widiastuti; Nugroho Agung Pambudi (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Academic dishonesty is a deliberate violation of academic rules for personal gain. Academic dishonesty can reduce the reputation of students and universities, as well as dishonest behavior in the world of work, so research is needed regarding engineering students' perceptions of academic dishonesty. This study aims to determine perceptions, experiences, reasons why engineering students commit academic dishonesty, and to determine the influence between perceptions and experiences of witnessing acts of academic dishonesty. The population used in this study were S1 students from the UNS Faculty of Engineering and the samples taken were 97 respondents. The results of the study show that engineering students' perceptions of academic dishonesty are that students know that academic dishonesty is important, can have an impact on damaging moral character, including actions that violate social and religious norms, so that it becomes the student's responsibility, and must be responsible for caring for the integrity of other students. . The experience of engineering students with academic dishonesty is that students have committed dishonesty but support existing policies, often use unauthorized material during exams, work on papers or articles without including references, and ask for help from seniors who have taken exams but rarely submit assignments properly. pay someone else to complete it and rarely miss out on group assignments. Academic dishonesty policies already exist but sanctions and supervision need to be tightened to reduce academic dishonesty. The reason engineering students commit academic dishonesty is because they don't get sanctioned or punished, the attitude of the lecturer, many friends who do this, will make grades better, difficulty working on questions, easy internet access and fear of failure and lack of study time. Most of the respondents committed academic dishonesty due to internal factors. There is a positive and significant influence between perception and experience of witnessing techniques on the experience of committing academic dishonesty. So that when the perception and experience of witnessing gets higher, they will not commit academic dishonesty.